Treatment Compliance among Patients with Hypertension and Type 2 Diabetes Mellitus in a Coastal Population of Southern India - Rao, Chythra R. (Int J Prev Med, 2014)
BACKGROUND: Hypertension and diabetes are major risk factors for cardiovascular and cerebrovascular disease. Adherence is a primary determinant of the effectiveness of treatment because poor adherence attenuates optimum clinical benefit and paves the way for complications. METHODS: The cross-sectional community-based survey was carried out among men and women aged 30 years and above in the field practice area of a medical college to assess treatment compliance with respect to hypertension and type 2 diabetes mellitus. The study comprised of 426 subjects, already diagnosed with hypertension (287) and type 2 diabetes mellitus (139). During house visits, data were collected by personal face-to-face interview using a pre-tested structured questionnaire. Compliance was determined by indirect methods, which included self-reporting and interviews with the patients. RESULTS: Compliance to hypertension treatment was found to be 82.2%, while 83.6% of individuals with type 2 diabetes mellitus were on regular medication. Among the individuals on regular medication, 88 (37.3%) of them had controlled blood pressure. Although the compliance was good, blood pressure control was not optimal. Adherence was better among females as compared with males. Literacy status and socio-economic background were not found to be associated with treatment compliance. High cost of treatment for hypertension (39.3%) and diabetes (30.4%) and asymptomatic nature of the disease were the most common reasons cited for not taking regular medications. CONCLUSIONS: Adherence to hypertension and diabetes treatment was good. High cost of medications and asymptomatic nature of the disease were the reasons identified among the non-adherent patients.